Sacral agenesis: a pilot whole exome sequencing and copy number study. Issue 1 (December 2016) - Porsch, Robert; Merello, Elisa; De Marco, Patrizia; Cheng, Guo; Rodriguez, Laura; So, Manting; Sham, Pak; Tam, Paul; Capra, Valeria; Cherny, Stacey; Garcia-Barcelo, Maria-Mercè; Campbell, Desmond
Abstract Background Caudal regression syndrome (CRS) or sacral agenesis is a rare congenital disorder characterized by a constellation of congenital caudal anomalies affecting the caudal spine and spinal cord, the hindgut, the urogenital system, and the lower limbs. CRS is a complex condition, attributed to an abnormal development of the caudal mesoderm, likely caused by the effect of interacting genetic and environmental factors. A well-known risk factor is maternal type 1 diabetes. Method Whole exome sequencing and copy number variation (CNV) analyses were conducted on 4 Caucasian trios to identify de novo and inherited rare mutations. Results In this pilot study, exome sequencing and copy number variation (CNV) analyses implicate a number of candidate genes, includingSPTBN5, MORN1, ZNF330, CLTCL1 and PDZD2. De novo mutations were found inSPTBN5, MORN1 and ZNF330 and inherited predicted damaging mutations inPDZD2 (homozygous) andCLTCL1 ( compound heterozygous). Importantly, predicted damaging mutations inPTEN (heterozygous), in its direct regulatorGLTSCR2 (compound heterozygous) and inVANGL1 (heterozygous) were identified. These genes had previously been linked with the CRS phenotype. Two CNV deletions, onede novo (chr3q13.13) and one homozygous (chr8p23.2), were detected in one of our CRS patients. These deletions overlapped with CNVs previously reported in patients with similar phenotype. Conclusion Despite the genetic diversity and the complexity of the phenotype, this pilot study identified genetic features common across CRS patients.